Assessment of peritoneal elastic laminal invasion improves survival stratification of pT3 and pT4a colorectal cancer: a meta-analysis. Issue 11 (30th August 2019) - Odate, Toru; Vuong, Huy Gia; Mochizuki, Kunio; Oishi, Naoki; Kondo, Tetsuo
Abstract : Evaluating peritoneal elastic laminal invasion (ELI) has been proposed as an additional assessment for pT3 colorectal cancers (CRC). Its clinical significance has not yet been established. We performed a meta-analysis to investigate the prognostic impact of ELI assessment for subcategorisation of pT3 CRC. We performed a search in three electronic databases. HR and its 95% CI for overall survival (OS) and disease-free survival (DFS) were calculated using the random effects model weighted by the inverse variance method. We identified six studies that met inclusion criteria out of an original 703 studies found with our database search terms. Our meta-analysis included 1925 patients with pT3 and pT4a CRCs. The presence of ELI in pT3 CRC was associated with shortened OS compared with ELI negative pT3 CRC (HR=1.76; 95% CI 1.21 to 2.55); whereas the DFS was not statistically significant (HR=1.79; 95% CI 0.91 to 3.52). Furthermore, pT4a patients' OS (HR=1.84; 95% CI 1.41 to 2.40) and DFS (HR=1.88; 95% CI 1.17 to 3.04) were even worse than the OS and DFS of pT3 ELI (+) patients. ELI is a useful marker for stratifying patients with pT3 or pT4a CRCs into three prognostically distinct groups. We recommend the subcategorisation of pT3 CRC by ELI for better prognostic assessment and treatment strategy of patients with CRC.